e-XTENSION: A Virtual Learning Environment (VLE) System for a State University - Cofino, Chester L.; Atillo, Guilbert Nicanor A.; Velos, Severina P. (International Journal of Computing Sciences Research, 2021)
Purpose - This study aimed to develop a virtual learning environment system for a state university extension office that captivated and stimulated learners' imagination anytime, anywhere, using any device. The design provided distance training to the community in livelihood/technical-vocational/skills training, basic education training, communication and dissemination of knowledge, and gender sensitivity training. Method - The development followed the CDIO Framework known as conceive, design, implement, and operate. An evaluation process was conducted using the ISO/IEC 9126-1 or the Software Evaluation Criteria rated by the IT experts. Results –Both experts strongly agreed on the system's usability, maintainability, and sustainability and are easy to use with robust functions and support.  The study found out that both experts recommended the utilization as they believed the system is beneficial in terms of academic learning objectives for the extension programs. Conclusion – The assessment of the IT experts from industry and academe helped in the rating of quality software. The CDIO framework is very efficient and effective that produced quality software products. Lastly, the system allows users to boost their training to upland areas fully and maximize time. Recommendation – It is highly recommended that other techniques may be used to improve the system. This would upgrade the developed system's current features, especially on video conferences, as it found out that the institution must have a suitable server for video conferences upon utilization. Thus, improvement or integration of available video conferencing platforms is recommended. Practical Implication - University may use the system for other academic activities such as classes, video conferences, and a different process that uses any of the communication tools. The University may formulate a policy on the usage of the system and how it is being used to any unit of the school.